The Contribution of Television to the Spanish Collective Imagination - Mateos Pérez, Javier (Universidad de Chile. Instituto de la Comunicación e Imagen, 2014)
The evolution of the Spanish television goes parallel with the History of Spain due to the essential role that this mass media has played in the collective life of the country. Consuming television has been one of the main socializing elements and the shared experiences concerning television have built a specific collective vision. Television has become a factor of cohesion and a referential link. The work examines the history of television in Spain because it is thought to be an original, singular model, that differs from other televisions. A model which was born as a public service but grew and transformed into a peculiar commercial television.